(untitled) (Journal of the College of Basic Education, 2024)
The study aimed to build a measure of leadership by faith for the supervisor of the specialty from the point of view of physical education teachers, and the researcher used the descriptive approach in the survey method to suit the nature of the research. Determining the research community by the intentional method represented by the physical education teachers in the six directorates of Baghdad education, whose number is (2642), while The research was extracted according to a scientific statistical method, amounting to (336), and it was divided into an exploratory sample of (36), a construction sample (100), and an application sample (200) male and female teachers. Data was extracted and processed, and the results were displayed and analyzed using the statistical bag (Spss). The most important conclusions reached by the research was that the measure of leadership by faith was built for the supervisors of the specialty from the point of view of teachers of physical education.